2018
DOI: 10.3390/rel9110361
|View full text |Cite
|
Sign up to set email alerts
|

Bad Religion as False Religion: An Empirical Study of UK Religious Education Teachers’ Essentialist Religious Discourse

Abstract: We argue that there is a well-intentioned—yet mistaken—definitional turn within contemporary cultural discourse in which ‘true’ religion, being essentially loving and peaceful, is distinguished from ‘false’ religion. Concerned with the possibility that this discourse might be prevalent in school Religious Education (RE), we surveyed practicing RE teachers within the United Kingdom (UK) on their beliefs about religion. We wanted to see how far the surveyed teachers evidenced a strand of contemporary cultural di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
10
1
1
Order By: Relevance
“…This led to Sofian questioning whether his father had advised him well. These findings correlate with Arweck and Nesbitt (2011, 37) who report that RE could cause confusion among pupils and with Smith, Nixon, and Pearce (2018) who suggest that learners do not trust what they are taught in RE.…”
Section: Constructing Religions As Un-britishsupporting
confidence: 87%
See 1 more Smart Citation
“…This led to Sofian questioning whether his father had advised him well. These findings correlate with Arweck and Nesbitt (2011, 37) who report that RE could cause confusion among pupils and with Smith, Nixon, and Pearce (2018) who suggest that learners do not trust what they are taught in RE.…”
Section: Constructing Religions As Un-britishsupporting
confidence: 87%
“…As teachers tend to construct religions through the prism of the World Religions Paradigm, they are likely to reproduce essentialist constructions of religions, which are regularly reified and objectified (CoRE 2018, 3;Smith, Nixon, and Pearce 2018). This may result in ill-informed discussions about the place and role of religion in people's lives and society (CoRE 2018, 3;Dinham and Shaw 2015, 4) and in discussions that may end up being fuelled by the mass media (Knott 2016, 18).…”
Section: What Is 'Religion'?mentioning
confidence: 99%
“…While the largest groups of atheist Respondents stated that religion should be taught positively (34.55%), there was a significant difference with the theist response level (69.40%). We have argued elsewhere (Smith et al 2018) that there is a tendency, in the face of the pressure for RE to develop social cohesion and foster tolerance, that RE teachers often sanitise and essentialise religions. This pressure may explain why so many, of whatever religious and irreligious persuasion, responded as they did to the 'religious is dangerous' and 'religions should be taught in a positive way' statements.…”
Section: Discussionmentioning
confidence: 99%
“…This study consisted of an online survey distributed using professional networks, Standing Advisory Councils on Religious Education (SACREs), and RE teacher social media groups (N = 465 after exclusions). Research from the larger study, concerned with RE teachers' beliefs about religion, can be found in Smith et al (2018). However, we have included, in this paper, questions relating to the perception of religion as dangerous, and whether religion should be taught positively, in order to cross-tabulate these responses with degree backgrounds and (ir)religious beliefs (see below).…”
Section: Scope and Methodologymentioning
confidence: 99%
“…Nesbitt notes how schools' good intentions for inclusivity 'illustrates the way in which education is open to becoming a means of legitimation of minority practices' (Nesbitt 2004, p. 65). Selective syllabus curation presents the unpalatable decision of whether non-benign expressions of religion have a place in an RE syllabus as much as benign ones (Smith et al 2018). Teaching about internal diversity in religious traditions can leave an impression that religions are internally fractured.…”
Section: Challenges To the Authentic Representation Of Religious Tradmentioning
confidence: 99%